PERAN KOMISI PENYIARAN INDONESIA DAERAH SUMATERA SELATAN DALAM MENGAWASI KONTEN SIARAN TELEVISI LOKAL DI KOTA PALEMBANG - Alfarizi, Dimas Fabian; Saputra, Sepriadi (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This study aims to analyze the role of the South Sumatra Regional Indonesian Broadcasting Commission (KPID) in supervising local television broadcast content in Palembang City. This research employs a qualitative field research method using interviews, observations, and documentation. The findings indicate that KPID South Sumatra conducts supervision through broadcast monitoring, guidance for broadcasting institutions, and public participation. The supervisory approach is predominantly corrective and educative; however, its effectiveness is constrained by limited resources and the challenges of broadcasting digitalization. Nevertheless, collaboration with various stakeholders presents an opportunity to strengthen a more participatory and sustainable local broadcasting supervision system.